Concrete Ways to Decolonize Research - Asselin, Hugo; Basile, Suzie (An International Journal of Critical Geographies, 2018)
« Almost 20 years after Māori scholar Linda Tuhiwai Smith’s call to decolonize research (Smith, 1999), significant progress has been made into drafting ethics principles to guide research with Indigenous people (e.g., CIHR et al., 2014). However, transforming principles into actual practices is easier said than done. It is increasingly recognizedthat “knowing the key guiding principles for research with Indigenous peoples is not always enough and [principles need to be]translated into day-to-day research practices”(Morton Ninomiya and Pollock, 2017, p. 29). This themed issue presents studies on various topics conducted in different geographical and cultural settings and suggesting concrete ways to decolonize research. The call for papers was issued following the 3rd Seminar on the ethics of research with Aboriginal people held at the Université du Québec en Abitibi-Témiscamingue in late 2014. Two previous editions of the seminar (in 2009 and 2011) had invitedparticipants2to share experiences of good and bad research practices, summarized in Asselin and Basile (2012). The 3rd seminar took a step further in focusing on concrete ways to decolonize research.In what follows, we discuss research decolonization and summarize the key messages from the keynote speakers of the 3rd seminar, some of which have contributed papers to this themed issue. Additional contributions widened the geographical scope considered (Canada, Mexico, Peru) in addition to providingmore examples of concrete ways to decolonize research. » [Extrait original p. 643-644|
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; autochtones; canada; décolonialisme; justice sociale; orpcc; outils; pour des recherches en milieux de pratiques; premiers peuples; périodes historiques; recherche en milieux de pratique; ressource en ligne; régions géographiques; système colonial; systèmes d'oppressions

La reconnaissance de l’homoparenté au Québec. Lorsque les stratégies de mobilisation de la communauté rencontrent l’avant-gardisme de l’État - Côté, Isabel; Lavoie, Kévin (Revue des politiques sociales et familiales, 2018)
Résumé Cet article retrace les jalons historiques ayant mené à l’institutionnalisation de l’homoparenté au Québec et met en lumière la synergie entre les revendications d’associations gaies et lesbiennes et les interventions étatiques de l’appareil gouvernemental. La décriminalisation de l’homosexualité au Canada en 1969, puis l’ajout de l’orientation sexuelle comme motif illicite de discrimination dans la Charte québécoise des droits et libertés en 1977 ont posé les bases juridiques sur lesquelles s’est ancrée la reconnaissance des couples de même sexe et des familles homoparentales aux tournants du nouveau millénaire. Les stratégies de mobilisation déployées par les groupes militants se sont alors inscrites dans les filières institutionnelles de l’action publique, à la rencontre des interventions progressistes de l’État québécois. L’analyse rétrospective de cette lutte offre une meilleure compréhension de la transformation des représentations familiales contemporaines et des débats actuels en matière de filiation.
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; LGBTQIA2+; amérique du nord; amériques; approches et analyses; canada; corps; cours; discipline; discours dominant; hétéronormativité; hétérosexisme; identités LGBTQIA2+; inégalités; justice sociale; maternité; parentalité; premier cycle; privilèges; périodes historiques; queer; québec; régions géographiques; sciences humaines; soc2262; soc2264; sociologie; systèmes d'oppressions; thématiques

Kiffe ta race - Binge Audio - Ly, Grace; Diallo, Rokhaya (Kiffe ta race - Binge Audio, 2018)
Pourquoi le mot « race » est-il tabou ? Qu’en est-il quand on est, à la fois, victime de discriminations raciales et sexuelles ? Comment assumer son identité plurielle ? Un mardi sur deux, Rokhaya Diallo et Grace Ly reçoivent un·e invité·e pour explorer les questions raciales sur le mode de la conversation et du vécu.
Keywords: 2000 à aujourd'hui; 2010-2019; 2020-2029; afro-féminisme; approches et analyses; care; com5170; communication; corps; cours; discipline; europe; france; identités; intersectionnalité; journalisme; justice sociale; militance; premier cycle; pédagogie; périodes historiques; racisme; régions géographiques; système colonial; systèmes d'oppressions; thématiques; théorie critique de la race; violences